Clinical outcome at 2 years following diagnosis of medium chain acyl coenzyme a dehydrogenase deficiency through newborn screening: findings from the prospective UK collaborative and british paediatric surveillance unit studies. (29th September 2015) - Oerton, J; Khalid, JM; Chakrapani, A; Champion, M; Cleary, M; Sharrard, M; Walter, J; Leonard, J; Andresen, BS; Dezateux, C
Abstract : Background: Newborn screening for medium chain acyl coenzyme A dehydrogenase deficiency (MCADD) has been implemented in a number of countries, including England (April 2009) but there are few reports of clinical outcome in large-scale prospective studies. During a UK pilot screening phase, all screen positive babies were followed through the British Paediatric Surveillance Unit (BPSU) to ascertain clinical outcome. Aim: To report the spectrum of screen-positive MCADD referrals over a 2-year period and clinical outcomes at 2 years following confirmed MCADD diagnosis. Methods: Between 1 March 2004 and 28 February 2006, 102 children were referred as presumptive positive (average triplicate screening C8 ≥0.5μmol/L) among 738 242 newborns screened at age 5–8 days (screen positive prevalence 1.4 per 10 000). Blood acylcarnitines, urine organic acids and c.985→G status, with extended mutation analysis in all non-c.985→G homozygotes (HMZ), were measured in all cases. Results were reviewed using an agreed diagnostic algorithm by an independent expert panel who assigned children to one of four categories: MCADD of definite phenotype; MCADD of uncertain phenotype; carriers; not MCADD. Clinician-reported clinical outcome at 1 and 2 years was obtained by systematic follow-up of new diagnoses notified to the BPSU. Results: Of 102 screen positive infants (12 Asian; 43 female), 86 were confirmed as MCADD (positive predictive value 84%): 60 of definite phenotype (47 c.985→G HMZ, 13 other genotypes of known pathogenicity); 26 of uncertain phenotype (all with genotypes of uncertain pathogenicity). 79/86 (92%) were notified to the BPSU, with complete follow-up in 76 and partial follow up in three. At 2 years, one serious clinical episode was reported, one child experienced apnoea following vaccination and one child was reported with developmental delay/poor growth. One child (c.985→G HMZ) died after the 2-year follow-up period (age 2 years 9 months) during an intercurrent illness. Conclusion: The specificity of screening is high and prevalence of c.985A→G homozygosity (55%) is comparable to other international screening programmes. While clinical outcome among screened babies appears good, death can occur highlighting the importance of timely management of acute illnesses in children with MCADD and effective information for and education of parents. Further information on longer-term outcomes is needed.